Lossless compression hand book - Khalid Sayood [ editor ] (Academic Press, 2006)
The book is probably the best technical reference on lossless compression ever published. All aspects of the book deserve kudos. It contains up to the date and to the point professional coverage of a wide field presented with an exceptional clarity. The balance between practical and theoretical aspects is excellent. The book is mostly self-contained thanks to the intro part on the basics of information and complexity theory. The intro, despite its modest size, is superior to many dedicated textbooks. The other three main parts discuss compression techniques, applications and standards. The chapters are written by different authors and, as can be expected, are not all equal in terms of depth or practical applicability. However, all of them provide a list of well selected references, which compensate for some of the shorter chapters. The editors and the authors did a great job on delivering the text which is quite uniform in style, highly informative and yet very readable and digestible throughout the entire book. Most methods are explained with enough details to start your own research or implementation. Whenever possible the authors compare different methods with tables and graphs. Thus, before a reader jumps into coding, (s)he can make an intelligent choice. (This, btw, comes from my personal experience. The next day after arrival the book helped me to find a better replacement for an inhouse method of encoding.) Practitioners will also appreciate discussion of patent issues and possible workarounds, when applicable. Bottom line - this is one of the most useful technical books I bought. A must have for anyone working with data compression.